2021
DOI: 10.3389/fpls.2021.702842
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Cape Gooseberry Plants to Fusarium oxysporum f. sp. physali, Fusaric Acid, and Water Deficit in a Hydrophonic System

Abstract: Cape gooseberry production has been limited by vascular wilt caused by Fusarium oxysporum f. sp. physali (Foph). Fusaric acid (FA) is a mycotoxin produced by many Fusarium species such as F. oxysporum formae speciales. The effects of the interaction between this mycotoxin and plants (such as cape gooseberry) under biotic stress (water deficit, WD) have been little explored. Three experiments were carried out. The objectives of this study were to evaluate (i) different Foph inoculum densities (1 × 104 and 1 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Similarly, FA treatment of Arabidopsis seedlings reduced root and root hair growth along with induction of membrane hyperpolarisation (Bouizgarne et al 2006b ). Similarly, FA-induced physicochemical changes such as reduced photosynthetic activity and plant biomass, turgor loss, as well as high proline content were observed in cape gooseberry plants at 100 mg/L FA concentration (Mendoza-Vargas et al 2021 ). In addition, higher oxidative stress and antioxidant activity and reduced cell viability were observed in tomato cell suspensions at 2 × 10 −4 M dose of FA.…”
Section: Fa-elicited Physiological Effectsmentioning
confidence: 88%
See 2 more Smart Citations
“…Similarly, FA treatment of Arabidopsis seedlings reduced root and root hair growth along with induction of membrane hyperpolarisation (Bouizgarne et al 2006b ). Similarly, FA-induced physicochemical changes such as reduced photosynthetic activity and plant biomass, turgor loss, as well as high proline content were observed in cape gooseberry plants at 100 mg/L FA concentration (Mendoza-Vargas et al 2021 ). In addition, higher oxidative stress and antioxidant activity and reduced cell viability were observed in tomato cell suspensions at 2 × 10 −4 M dose of FA.…”
Section: Fa-elicited Physiological Effectsmentioning
confidence: 88%
“…FA concentration between 50 and 200 mg/L resulted in lipid oxidation, and significantly increased the MDA content in wheat and faba bean seedlings (Li et al 2021 ). Similarly, FA exposure at a concentration of 100 mg/L increased the MDA level in cape gooseberry plant after 12 h (Mendoza-Vargas et al 2021 ). Further, other studies also showed that exposure of watermelon to FA (0–400 mg/L) increased MDA levels at 24 h. The MDA content significantly increased with the duration of FA exposure, reaching a maximum (5–11-fold) at 24 h post treatment as compared to control plants (Wu et al 2008b ).…”
Section: Fa-mediated Lipid Peroxidationmentioning
confidence: 93%
See 1 more Smart Citation
“…by Chitarra et al [59] just before visible plant withering. Under Fusarium wilting stress, the leaf apparatus is a recipient through the xylem of toxins secreted by the pathogen into the vessels (i.e., fusaric acid), which play a crucial role in damaging mesophyll cell membranes and chloroplasts due to the occurrence of oxidative stress [60][61][62], resulting in the suppression of all related photosynthesis processes, the development of leaf chlorosis, and yellowing [63]. While plant physiological responses to water shortage, which in the long run leads to leaf curling, wilting, and the appearance of necrosis, are somewhat more delayed than the abovementioned pigmentation anomalies due to the activation of plant self-protective mechanisms (i.e., stomatal closure, accumulation of proline, abscisic acid, and soluble sugars) according to the study by Sun et al [64] on cucumber infected by Fusarium oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…These agents can disrupt normal metabolism, plant growth, and yield [53]. In Colombia, one of the most limiting biotic agents in cape gooseberry crops is Foph, which is the species that causes vascular wilt, showing a wilt incidence greater than 50% in the production areas [54]. Alternatives based on biological control have become very important for the P. peruviana-Foph pathosystem in Colombia [11,38,45].…”
Section: Introductionmentioning
confidence: 99%